2008
DOI: 10.4103/1596-3519.55668
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of epistaxis in Sokoto, Nigeria: A review of 72 cases

Abstract: Background: Epistaxis remains a common otorhinolaryngological emergency in most hospital emergency departments with varied manifestations. The pattern as seen in a tertiary health institution in sokoto, Nigeria is the subject of this paper. Method: This is a 5year retrospective study (January 1995-December 1999 of all cases of epistaxis presenting at or referred to the Ear, Nose and Throat (ENT) Department of Usmanu Danfodiyo University Teaching Hospital (UDUTH) Sokoto, Nigeria whose data were analyzed. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
41
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 9 publications
13
41
1
Order By: Relevance
“…(11) In this study, surgical treatment was done only in 0.87% of patients who presented with bleeding intranasal tumor with 100% success rate. Similar finding was also reported in Iseh Kr et al (25) In our series, no surgical ligation of vessel was required. Arterial ligation is necessary in intractable cases of epistaxis when conservative measures fail.…”
Section: Discussionsupporting
confidence: 79%
“…(11) In this study, surgical treatment was done only in 0.87% of patients who presented with bleeding intranasal tumor with 100% success rate. Similar finding was also reported in Iseh Kr et al (25) In our series, no surgical ligation of vessel was required. Arterial ligation is necessary in intractable cases of epistaxis when conservative measures fail.…”
Section: Discussionsupporting
confidence: 79%
“…Earlier report from Nigeria also showed that some patients had epistaxis when their HT was not controlled due to cessation of antihypertensive drug therapy. 9 Varshney and Saxena 5 recorded hypertension as the second commonest cause of epistaxis after idiopathic causes in India, while Chaiyasate et al 2 reported hypertension to be the commonest cause of epistaxis followed by idiopathic causes in Thailand. The need for regular blood pressure check-up and compliance to antihypertensive medications must be emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…KR, 13 Klossek, 14 Hussain G, 15 and Middleton P et al 16 all leading to same pattern throughout the world favoring anterior bleeding.…”
mentioning
confidence: 99%